2004
DOI: 10.1038/sj.bjp.0705685
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 receptors stimulate AKT phosphorylation in astrocytes

Abstract: 1 Emerging evidence indicates that nucleotide receptors are widely expressed in the nervous system. Here, we present evidence that P2Y and P2X receptors, particularly the P2X 7 subtype, are coupled to the phosphoinositide 3-kinase (PI3K)/Akt pathway in astrocytes. 2 P2Y and P2X receptor agonists ATP, uridine 5 0 -triphosphate (UTP) and 2 0 ,3 0 -O-(4-benzoyl)-benzoyl ATP (BzATP) stimulated Akt phosphorylation in primary cultures of rat cortical astrocytes. BzATP induced Akt phosphorylation in a concentration-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(75 citation statements)
references
References 78 publications
(109 reference statements)
7
68
0
Order By: Relevance
“…As shown in Fig. 3, a short incubation of macrophages with ATP caused Akt phosphorylation to increase significantly, consistent with previous reports in macrophages and astrocytes (8,27). The increase in Akt phosphorylation could be inhibited by co-treatment of macrophages with NAC (Fig.…”
Section: Extracellular Atp Induces Ros Production In Primarysupporting
confidence: 80%
See 1 more Smart Citation
“…As shown in Fig. 3, a short incubation of macrophages with ATP caused Akt phosphorylation to increase significantly, consistent with previous reports in macrophages and astrocytes (8,27). The increase in Akt phosphorylation could be inhibited by co-treatment of macrophages with NAC (Fig.…”
Section: Extracellular Atp Induces Ros Production In Primarysupporting
confidence: 80%
“…Ligation of Purinergic Receptors Leads to Activation of the PI3K Pathway-Extracellular ATP can activate PI3K in macrophages and other cell types (6,8,27). In many cell types, PI3K phosphorylates and activates the downstream Ser/Thr kinase, Akt/PKB, which promotes survival or controls metabolism through phosphorylation of multiple targets (28).…”
Section: Extracellular Atp Induces Ros Production In Primarymentioning
confidence: 99%
“…Alternatively, P2X7R stimulation may activate two independent pathways, involving Src family tyrosine kinase(s) and PI3K, both leading to MEK1/2 activation. Jacques-Silva et al (61) have recently shown the activation of Akt via PI3K and Src family kinases in P2X7R-stimulated rat astrocytes. This observation contrasts with our finding that Akt is not phosphorylated in ATP-treated thymocytes, despite PI3K activation.…”
Section: Discussionmentioning
confidence: 98%
“…The GFAP-positive progenitor cells investigated in this study were multipotential and expressed the stem-cell marker nestin as well as the type-B cell-associated ectonucleotidases NTPDase2 and TNAP (Mishra et al, 2006;Langer et al, 2007), suggesting that they represent type-B cell-like neural precursors. Both RT-PCR and pharmacological experiments suggest that cultured astrocytes express a variety of P2Y and P2X receptors (Jacques-Silva et al, 2004;Washburn and Neary, 2006) whose functional impact is only partially understood. We have identified several P2 receptors (P2X and P2Y) in cultured adult neural progenitor cells but the RT-PCR data alone do not allow conclusions regarding the extent of translation and amount of functional protein.…”
Section: The Molecular Features Of Neural Progenitors Only Partially mentioning
confidence: 99%
“…In murine astrocytes, P2Y 6 mRNA was found to be absent (Lenz et al, 2000) whereas P2Y 4 receptor mRNA could be identified, in contrast to neural progenitors. Cultured astrocytes express the P2X 7 receptor and activation of this receptor stimulates Akt phosphorylation (Jacques-Silva et al, 2004), but P2X 7 receptor mRNA is essentially absent from cultured neural progenitors. The notion that the molecular features of neural progenitors only partially overlap with those of astrocytes is also supported by our observation that the fingerprint of ERK1/2 and CREB phosphorylation induced by ADPβS, UTP and EGF differs between neural progenitors and progenitor-derived astrocytes.…”
Section: The Molecular Features Of Neural Progenitors Only Partially mentioning
confidence: 99%